The Science of Social Vision 2010
DOI: 10.1093/acprof:oso/9780195333176.003.0004
|View full text |Cite
|
Sign up to set email alerts
|

Faces, Bodies, Social Vision as Agent Vision, and Social Consciousness

Abstract: and KeywordsThis chapter discusses recent findings from research on face and body perception giving special attention to the implications of the findings for social vision. The first section is devoted to similarities between the processes underlying face and body perception. The second section discusses how the perception of faces and bodies is integrated. The third section tackles issues on conscious and nonconscious perception of socially meaningful signals and their neuroanatomical underpinnings. Finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 98 publications
(149 reference statements)
1
6
0
Order By: Relevance
“…This is consistent with previous work in emotion recognition, which showed that the combination of faces and bodies were judged more accurately than either alone (de Gelder and Tamietto 2011;Meeren et al 2005). The accuracy of judgments from the full and outline bodies in studies 2a and 2b, respectively, might have therefore been enhanced by the combination of information from the body and head.…”
Section: Study 2c Results and Discussionsupporting
confidence: 90%
“…This is consistent with previous work in emotion recognition, which showed that the combination of faces and bodies were judged more accurately than either alone (de Gelder and Tamietto 2011;Meeren et al 2005). The accuracy of judgments from the full and outline bodies in studies 2a and 2b, respectively, might have therefore been enhanced by the combination of information from the body and head.…”
Section: Study 2c Results and Discussionsupporting
confidence: 90%
“…Recently, de Gelder and Tamietto (2010) reviewed the evidence for the existence of very early social vision, in which processing may begin already in subcortical structures. As evidence, they highlight work showing that body language, visual scenes, and vocal cues all influence the processing facial displays of threat (Meeren, Hvan, Heijnsbergen, & de Gelder, 2005), even at the earliest stages of face processing and across conscious and nonconscious processing routes (de Gelder, Morris, & Dolan, 2005).…”
Section: Social Visual Perceptionmentioning
confidence: 99%
“…Hence, this also provides a valuable testing ground for gaging cross-species continuity of functions and comparison. Secondly, examining stimulus properties and categories that evoke Amg activity without awareness, or that by comparison fail to do so, we may be able to abstract from common taxonomies, such as those distinguishing animate from inanimate objects, faces from bodies and so on, to reveal cross-category commonalities between stimulus types and attributes that could not be anticipated by looking at cortical segregation of stimulus categories (de Gelder and Tamietto, 2011; Van den Stock et al, 2014). Lastly, the Amg clearly rests at the intersection between conscious as well as non-conscious emotional processing (Pessoa and Adolphs, 2010).…”
Section: Introductionmentioning
confidence: 99%